Dynamic 4D-CT Angiography for Guiding Transarterial Chemoembolization: Impact on the Reduction of Contrast Material, Operator Radiation Exposure, Catheter Consumption, and Diagnostic Confidence - Albrecht, Moritz H.; Vogl, Thomas J.; Wichmann, Julian L.; Martin, Simon S.; Scholtz, Jan-Erik; Fischer, Sebastian; Hammerstingl, Renate M.; Harth, Marc; Nour-Eldin, Nour-Eldin A.; Thalhammer, Axel; Zangos, Stephan; Bauer, Ralf W. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose This study was carried out to investigate the impact of abdominal dynamic four-dimensional CT angiography (4D-CTA) for guiding transarterial chemoembolization (TACE) on the amount of contrast material used, operator radiation exposure, catheter consumption, and diagnostic confidence.Materials and Methods Written consent was waived for this IRB-approved retrospective study. 29 patients (20 men; mean age: 65.7 ± 11.5 years) with malignant liver lesions underwent 4D-CTA, prior to initial TACE. Time-resolved volume-rendering technique (VRT), maximum-intensity projection (MIP), and multiplanar reconstruction (MPR) series were reconstructed, enabling a direct selective catheterization of the tumor-supplying artery without prior conventional digital subtraction angiography (DSA). 29 patients (16 men; mean age: 69.4 ± 13.9) who underwent traditional TACE served as the control group. The amount of administered contrast media, operator radiation exposure, and catheter consumption during TACE were compared. Two radiologists assessed diagnostic confidence in the exclusion of portal vein thrombosis.Results 4D-CTA TACE resulted in a significant reduction in the amount of contrast media used, compared to traditional TACE (–61.0 ml/ –66.3 % intra-arterial, –12.8 ml/ –13.8 % overall; P < 0.001). The dose-area product indicating operator radiation exposure during intervention was reduced by 50.5 % (P < 0.001), and 0.7 fewer catheters on average were used (P = 0.063), while 4D-CTA data was available to guide TACE. Diagnostic confidence in the exclusion of portal vein thrombosis was significantly enhanced by 4D-CTA, compared to traditional DSA images (scores, 3.9 and 2.4, respectively; P < 0.001).Conclusion Dynamic 4D-CTA enables TACE with a substantially reduced amount of contrast material, decreases operator radiation exposure, and increases diagnostic confidence in the exclusion of portal vein thrombosis.Key points Citation Format
Keywords: abdomen; chemoembolization; CT; radiation safety; contrast agents